Relevance of B3 lesions in breast diagnosis – frequency and therapeutic consequences - Madjar, Christin; Seabert, James; Fisseler-Eckhoff, Annette; Gustmann, Christian; Hoffmann, Isabell; Lünstroth-Lenk, Doris; Rinast, Edgar; von Bruchhausen, Carla; Madjar, Helmut; Hoffmann, Gerald (Senologie - Zeitschrift für Mammadiagnostik und -therapie, 2018)
With improvements in breast imaging and minimally invasive interventions, detection of early breast cancer has increased. However, with the improved diagnostic capabilities, the risk of false-positive benign lesions as well as lesions classified as B3 by histopathology has also increased. Varying rates of malignancies are associated with B3 lesions, raising the question of whether such lesions should always be surgically removed. The results of our retrospective analysis should assist in this decision-making process.307 core needle or vacuum-assisted needle biopsies in which B3 lesions were found were examined. The most common lesions were intraductal papillomas (44 %), atypical ductal hyperplasia (22.8 %), flat epithelial atypia (9.4 %), phyllodes tumours (6.5 %), radial scars (5.9 %), LIN 1 (4.9 %), complex fibroadenomas (3.3 %) and LIN 2 (1.6 %). The frequencies depended considerably on whether the tissue was obtained by core biopsy or vacuum biopsy. Stereotactic vacuum biopsy was generally performed in the case of microcalcification not apparent on sonography. Lesions visible on ultrasound had core needle biopsy.Surgery was performed in 254 cases and a malignancy was found in 27.2 % on the final histopathology. Malignancy was found in 24.6 % of 114 cases initially diagnosed as intraductal papilloma. Similarly, cancer was discovered in 48.4 % of the 62 cases of atypical ductal hyperplasia, in 2.4 % of the 41 cases of flat epithelial atypia, complex fibroadenoma and phyllodes tumour, in 20.7 % of the 29 cases of LIN 1 and radial scar as well as in 50 % of the 8 cases of LIN 2, adenomyoepithelioma and atypical apocrine metaplasia.These data indicate the necessity for complete surgical removal of a B3 lesion when it is discovered using the core needle or vacuum-assisted biopsy technique. The decision not to perform surgery can be made when the risk of associated malignancy is deemed low in the clinical pathology conference, but careful follow-up is essential.Fortschritte in der bildgebenden Brustdiagnostik und die Einführung von minimalinvasiven Nadelbiopsien haben neben einer besseren Brustkrebsfrüherkennung auch die Zahl falsch positiver benigner Befunde und die Entdeckung von sogenannten Risikoläsionen erhöht. Letztere werden histologisch als B3-Läsionen eingeteilt. Hinter diesen verbergen sich in unterschiedlicher Häufigkeit Malignome, sodass die Entscheidung zu einer Operation oft kontrovers diskutiert wird. Mit der Auswertung unserer Ergebnisse im Rahmen einer retrospektiven Studie wollen wir eine Entscheidungshilfe liefern.Insgesamt wurden 307 Stanz- oder Vakuumbiopsien (VSB) durchgeführt, die eine B3-Läsion ergaben. Die häufigsten Befunde waren: Papillome (44 %), ADH (22,8 %), FEA (9,4 %), Phylloidestumoren (6,5 %), radiäre Narben (5,9 %), LIN 1 (4,9 %), komplexe Fibroadenome (3,3 %) und LIN 2 (1,6 %). Die Häufigkeiten variierten erheblich in Abhängigkeit davon, ob die Abklärung durch Stanzbiopsie oder VSB vorgenommen wurde. Die stereotaktisch geführte VSB wurde in der Regel bei radiologischem Mikrokalk ohne sonografisches Korrelat durchgeführt. Sonografisch auffällige Befunde wurden dagegen durch die Stanzbiopsie abgeklärt.In 254 Fällen erfolgte eine Operation, die in 27,2 % der Fälle eine bösartige Histologie ergab: 24,6 % der 114 Papillome, 48,4 % der 62 ADH, 2,4 % der insgesamt 41 FEA, komplexen Fibroadenome und Phylloidestumoren, 20,7 % der 29 LIN-1-Läsionen und radiären Narben sowie 50 % der 8-LIN-2-Läsionen, Adenomyoepitheliome und atypischen apokrinen Metaplasien.Daraus folgt, dass die Indikation zur offenen Biopsie nach einer Nadelbiopsie mit dem Ergebnis einer B3-Läsion grundsätzlich gegeben ist. Jedoch kann in Einzelfällen insbesondere bei geringerer Malignomrate nach klinisch-pathologischer Konferenz und kritischer Bewertung der bildgebenden Diagnostik auf die Operation verzichtet werden. Ein sorgfältiges Follow-up ist aber unabdingbar
Keywords: B3 lesions; uncertain malignant potential; open breast biopsy; breast cancer risk; interventional diagnostics